1989
DOI: 10.1007/bf01954858
|View full text |Cite
|
Sign up to set email alerts
|

An improved immunohistostaining procedure for peptides in human brain

Abstract: Floating sections from human brains immersed for more than forty years in formalin, or from brains freshly fixed for a short time are treated by KMnO4-Pal's modified solutions to suppress the endogenous peroxidase activity before using the peroxidase-antiperoxidase method (PAP), or to remove the autofluorescence of lipofuscin, which is very intense in brains from old patients, before using the immunofluorescence method. Following this, immersion of sections in NaOH and H2O2 allows for the demasking of antigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Previous works (Ramos-Vara, 2005;Liu et al, 2010) reported that the use of retrieval-antigen systems can recover the loss of immunolabeling, thus we have performed a protocol that includes the retrieval of antigens by strong alkaline treatment (Guntern et al, 1989). This protocol has been successfully used by our group for detection of neuropeptides and proteins in the same human brains (Graterón et al, 2003;Insausti et al, 2010;Coveñas et al, 2014;Cebada-Sánchez et al, 2014), providing a good morphological preservation of the tissue.…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…Previous works (Ramos-Vara, 2005;Liu et al, 2010) reported that the use of retrieval-antigen systems can recover the loss of immunolabeling, thus we have performed a protocol that includes the retrieval of antigens by strong alkaline treatment (Guntern et al, 1989). This protocol has been successfully used by our group for detection of neuropeptides and proteins in the same human brains (Graterón et al, 2003;Insausti et al, 2010;Coveñas et al, 2014;Cebada-Sánchez et al, 2014), providing a good morphological preservation of the tissue.…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…In order to avoid possible interference by endogenous peroxidase, free-floating sections were treated with a mixture of NH 3 , NaOH and H 2 O 2 for 20 min (Guntern et al, 1989). Then, the sections were washed in PBS (3 Â 10 min) and pre-incubated for 30 min in PBS containing 1% normal horse serum and 0.3% Triton X-100 in order to enhance antibody penetration.…”
Section: Immunocytochemical Techniquementioning
confidence: 99%
“…Thioflavin-S fluorescence was optimally observed using the UV filter set described below (U-filter). Unless otherwise noted, in this and all fluorescent staining procedures, inherent tissue autofluorescence from endogenous lipofuscin was minimized using a quenching step based on oxidative methods of lipofuscin modification (Barden 1983(Barden ,1984Guntern et al 1989). …”
Section: Autofluorescence Quenching Procedures and Thioflavin-s Stainingmentioning
confidence: 99%